Immediate unitary fixed restoration with natural crown - Bouabid, Morchad (Eastern Journal of Medical Sciences, 2019)
Post extraction of anterior teeth, and in order to find the esthetics and the fundamental functions in the immediate future, there is an original technique whose aesthetic result is incomparable since the absence of teeth will be restored by the crown of the tooth to be replaced, and will be kept in place thanks to the composite reinforced glass fibres.